Synthetic opera: transcending contradictions of post-logical construction. (6th January 2011) - Robbins, Felix
This article speculates on the potential of multiple and synthetic approaches to architectural design. The argument is developed from current PhD research on the construction of "an architectural project". It investigates the status of instruction and construction of "project" in the context of describing the synthetic process and the speculative product of emerging design work. The article investigates the process of "constructing" architectural design (intellectually and physically) and the notion of a necessary dissolution of this construction. This dissolution is suggested as a necessary and contingent aspect of construction that facilitates a projection beyond the limitations of its initiating conception. The consequent argument is that this projection "beyond" offers the potential, through integration with lived experience and contingent actualised adjustment and evaluation, to "transcend" the problematic of a post-logical absence of architectural relevance. Post-logical is used to articulate the movement beyond singular axiomatic principles, universalising value structures and self-legitimising narratives. It is established in the article as the contemporary context of "absence" and relativity. The article proposes a projective and speculative architecture that through an intensity of synthetic designing defines the possibility of contingent value within (and despite) this context. It considers the design potential of not a singular model of instruction that is described by a static logic of theoretical construction, but proposes a multiple and involving field of instructional strategies of intervention and speculation. It proposes working severally to transcend the ungrounded legitimacy of the singular model of architectural discipline. Proposing an "opera" of synthesis rather than a singular work where intense and involving contingencies design ecologies move between positions and allow the construction of an architectural project to be "exposed". The article argues for the active practice of models for i.e. designing as interventions and synthetic operations that move between positions and become genuinely "instructional". This proposal is offered as an alternative "way of working". It is presented in contrast to the conventional model of a static representation and theoretical illustration that typically simply reinforce the contradictions of a post-logical cultural context.